Statistical Analysis of Reducing Biochemical Oxygen Demand (BOD) on Industrial Rubber Wastewater Using Dielectric Barrier Discharge Plasma - Abdul SYAKUR; Badrus ZAMAN; Dias Yunita NURMALIAKASIH (IAES Indonesia Section, 2016)
Dielectric Barrier Discharge plasma (DBD) is one of type non-thermal plasma (non-equilibrium plasma) or can be referred to as cold plasma. In this research, DBD plasma be utilized to reduce organic compounds like Biochemichal oxygen demand in the wastewater rubber processing. In the environment field DBD plasma has been used as a treatment for reducing air pollutants such as gas COx, NOx and HC. In addition DBD plasma have been developed to processed wastewater as an alternative technology in wastewater treatment. DBD plasma appears when the electrode is given a high voltage so that, it will form electric field in the area of the electrodes which allows the ionization and the presence of high-energy electrons in the area. The presence of these electrons will ionize molecules of H2O into active species such as OH•, H• and H2O2. The active species that can oxidize into CO2 and H2O so, BOD that can be degraded. In this research for wastewater treatment used high voltage are 10kV, 11kV, 12kV and 13kV and variations of processing time for 5, 10, 15, 20, and 25 (minutes). By increasing the voltage and extend the contact time then the speed variation of electrons to ionize the greater and more active species to be formed to degrade the pollutants to the maximum. This research used quantitative analysis with statistical analysis using SPSS software.